Application of Project-based Learning for Primary Teachers - A New Direction in Professional Training at Pedagogical Universities and Colleges in Vietnam - Bui, Thi Tam (International Journal of Psychosocial Rehabilitation, 2020)
Teaching staffs in general and primary teachers in particular have been proven to contribute to great success of the comprehensive renovation process in the current Vietnamese education system. Significantly, pedagogical universities specialized in primary education should predominantly pay attention to the quality of training and meet the requirements of society. In the case of Tay Nguyen University in Vietnam, lecturer staffs involved in training of primary teachers have made great efforts in applying new teaching methods. Furthermore, it has been used effectively in many parts of the primary teacher training program is the project-based learning method. In this paper, in addition to general theories about the project-learning method, we will present the advantages of applying the teaching method in the primary teacher training program in general and in the "Crafts and Techniques" module in particular at Tay Nguyen University. Finally, discussion process of applying project- based learning and project evaluation methods of primary education students in teaching this module are preferred.